From an eco-fairy tale to an environmen-tally friendly lifestyle.An eco-friendly reading project by Agnieszka Marzęcka - KAPUSTA, ANNA (Journal of Education Culture and Society, 2020)
The article is concerning on the eco-critical literary phenomenon on the perspective of new species polish eco-fairy tale. The fabulous tale about ecological style of life (The meta-phorical ecology of human biography) was ilustrated by the Agnieszka Marzęcka’s modernity tune entitled The Victory of King of Cleanness